AllPlay Dance: Two Pilot Dance Projects for Children With Disability, Developed and Assessed With a Dance Studies Approach - Millard, Olivia; Lindor, Ebony; Papadopoulos, Nicole; Sivaratnam, Carmel; McGillivray, Jane; Rinehart, Nicole (Frontiers in Psychology, 2021)
AllPlay Dance is founded on a collaborative approach to research between the School of Psychology and the School of Communication of Creative Arts, both of Deakin University. The research is also undertaken in partnership with professional ballet company, Queensland Ballet. This paper gives an overview of the two programs we developed in 2018 and 2019 for children with Cerebral Palsy (CP) and Autism Spectrum Disorder (ASD). Participants with disability ranged in age from 7-12 years. As well as describing the approach to the program development, we will discuss the inclusion of older and more experienced buddies as a method to support the participation in dance of children with developmental challenges, the diffusion of authorship in the making of group dances as a tool for inclusion, and the premise of dance as a social practice in which participants inter-subjectively generate meaning and sense making. The AllPlay Dance programs were developed as a series of dance classes in which participants worked with set or learned movement material, dance improvisation, and tasks for movement generation in order to collectively generate a dance for performance. While the benefit of participating in dance activities for children with disability was rigorously measured, (and will be reported elsewhere), this paper focuses on a secondary, longer-term aim of developing inclusive approaches to dance classes that challenge “ableist” notions of dance- as -spectacle and enable to work towards building transferable programs to allow all children who so desire, to participate in dance in their communities.